THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AND WORK MOREST THROUGH WORK MOTIVATION INTERVENING VARIABLES AT CV. PRIMA PRICE - Azhari, Saiful; Rafiki, Ahmad; Effendi, Ihsan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This research aims to analyze the influence of leadership style and work enthusiasm on employee performance, with work motivation as an intervening variable. The study employs a quantitative research approach, utilizing Structural Equation Modeling Partial Least Squares (SEM-PLS) for data analysis. The research was conducted at CV. Harsa Prima, a company engaged in multimedia technology, with a total sample of 42 employees. The findings indicate that leadership style positively affects work motivation, with a coefficient value of 0.609, and also positively impacts employee performance, with a coefficient value of 0.375. Additionally, work motivation has a positive effect on employee performance, with a coefficient value of 0.442. Furthermore, leadership style positively influences work morale, with a coefficient value of 0.44, while work motivation also significantly impacts work morale, with a coefficient value of 0.51. The study further reveals that work motivation significantly mediates the relationship between leadership style and work morale, as indicated by a T-statistic of 1.862 (>1.647) and a P-value of 0.032 (1.647) and a P-value of 0.036 (